Pengembangan buku ajar pembuatan kemeja pria dan efektivitasnya bagi siswa kelas XI Tata Busana SMK di Kabupaten Gunungkidul - Suharti Suharti; Agustina Sri Purnami (Bulletin of Educational Management and Innovation, 2024)
Background: Textbooks are essential in facilitating independent and structured learning for students, supporting teachers in delivering curriculum-aligned material, and ensuring vocational high school students gain relevant industry skills for effective knowledge transfer and achievement of learning objectives. Purpose: This study aims to produce textbooks for making men's shirts that are worthy of being used as instructional materials and to know the effectiveness of using textbooks for students of class XI at SMK Negeri Gunungkidul District. Method: This study is research and development (R&D) with reference to the Borg and Gall development model, namely:1) Conducting product analysis, 2) Developing initial products, 3) Expert validation and revision, 4) Small-scale field trials and product revisions, 5) large scale field trials and final products. The product trial design consists of media experts and material experts, as well as field trials. Data collection techniques are, observation, questionnaires and tests. The feasibility test of teaching books was analyzed using descriptive analysis. Whereas to test the effectiveness of textbooks, data were analyzed using the t-test with a significance level of 0.05.   Findings: The results showed that textbooks for making men's shirts were categorized as feasible, with the assessment of media experts getting an average score of 4.6 and based on the assessment of material experts, they got an average score of 4.28. The resulting textbook is effective to be used for students of Class XI Fashion Design at SMK N 1 Saptosari, as evidenced by the average pretest value of 64.12 increasing in the posttest of 83.21, the result of tcount ≥ t table (22.028≥ 1.696).